Den kultiverade spektatören eller striden om den goda smaken - Nordmark, Dag (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
Historical studies concerning the composition, social recruitment and behaviour of theatre audiences appear to possess a certain ethnological interest, in that they further elucidate particular cultural patterns. The present essay concerns theatre audiences in a number of small Swedish towns during the first half of the 19th century, and discusses both some of the factors which influenced their composition, and the antagonistic relationship which existed between different audience groups. The latter is interpreted as a struggle for cultural hegemony, comparing both aesthetic values and forms of behaviour in the auditorium.